Optimizing Placement of Automatic Sectionalizers in Distribution System Using Genetic Algorithm - Tran, Manh Hung; Tran, Manh Tri; Nguyen, Xuan Tung (Old Journal, 2020)
In recent years, improving the reliability of the distribution power system is one of the most concerned problems of the power utilities. This paper presents the strategy to deal with the problem of automatic sectionalizers placement in radial distribution feeders. Specifically, the genetic algorithm is used to find out the optimized location of automatic sectionalizers on a medium-voltage feeder of northern power distribution system in Vietnam. This study aims to improve the reliability of the distribution network by reducing the SAIDI and ENS indices.